An Overview of Neonatal Admissions at College of Medical Sciences (COMS) - Gurubacharya, SM; Gurubacharya, RL (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> mother 11.6568 <![endif]–><!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Objective: To know the profile of newborn admissions and its outcome and the factors associated with neonatal mortality. Methods: The study included both intramural and extramural cases of 180 newborn babies admitted in nursery over a period of 6 months from 01/08/06 to 31/01/07. The relevant data were recorded on a pre-designed proforma meticulously. Results: There were 180 newborn babies during the study period. The mean birth was 2.7 kg.. Majority, 77.8 %( 140) of the babies weighed equal to or more than 2.5 kg. Low birth weight (LBW) was seen in 22.2 %( 40) babies. There were 80 %( 144) full term babies and 20 %( 36) preterm babies. Majority of the mothers in the age group between 20-30 years had incomplete antenatal check- ups. There were 86 %( 155) normal vaginal deliveries, 4.5 %( 8) forceps deliveries and 9.5 %( 17) caesarean sections. Birth/perinatal asphyxia 39(22%), prematurity 36(20%) and neonatal septicemia 30(17%) comprised of leading admissions. There were 27deaths (15%) in total.13 (7%), 8(5%) and 6(3%) babies died of severe perinatal asphyxia, neonatal septicemia and prematurity respectively. Most of the deaths occurred during the first 72 hours. Conclusions: The mean birth weight is good. The major causes of neonatal death are birth/perinatal asphyxia, prematurity and neonatal septicemia. The factors influencing neonatal mortality are low and poor antenatal care, meconium stained liquor, delay in coming to the hospital, PROM, eclampsia. The study emphasises the importance of regular antenatal care, timely referral of pregnant women with complications to appropriate centers and conducting delivery in a clean environment for lowering neonatal mortality. Key words: newborn, admission, neonatal outcome, asphyxia doi:10.3126/jnps.v27i2.1413 J. Nepal Paediatr. Soc. Vol.27(2) p.73-74